Population and management models for the Swedish wild boar (Sus scrofa) - Magnusson, Madeleine (SLU/Dept. of Ecology, 2010)
The wild boar Sus scrofa population in Sweden has increased rapidly in the last decades which has led to conflicts among stakeholders, for example due to crop damages in agriculture. Thus, there is an urgent need of quantified goals and effective strategies for wild boar management. To develop such strategies, knowledge on population dynamics is fundamental. In this study a deterministic matrix model was used to estimate population growth, based on previously published data. The exponential growth rate for a wild boar population was calculated to 1.48. Elasticity analysis indicated that a change in juvenile survival has the strongest potential impact on population growth. With the present Swedish population estimated to at least 150 000 wild boar and the growth rate 1.48, a net increase of 72 000 boar has to be shot annually to keep the population at equilibrium. Further, harvest simulations were made to investigate the effects of varied cull among animal categories on growth rate and total harvest levels. In a model where proportional harvest of adult females was increased from 0.0 to 0.4 (combined with harvest of juveniles), the total harvest needed for a stable population decreased with 45 %. The corresponding model using adult males resulted in higher harvest levels. The effect on growth rate from varying combinations of proportional harvest of juveniles and of adult females was also illustrated by contour curves for λ at different levels (increase-stable-decrease population). However, implementation of theoretically developed strategies meets various obstacles, when e.g. ethics and practical issues are considered, and such applied aspects were discussed.